2014
DOI: 10.1182/blood-2014-01-552463
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant overexpression of CD14 on granulocytes sensitizes the innate immune response in mDia1 heterozygous del(5q) MDS

Abstract: Key Points• mDia1 deficiency led to a cellautonomous overexpression of CD14 on granulocytes and a hypersensitive innate immune response.• mDia1 heterozygous and knockout mice developed age-dependent MDS that was accelerated by chronic stimulation of the innate immunity.The myelodysplastic syndromes (MDSs) include a spectrum of stem cell malignancies characterized by an increased risk of developing acute myeloid leukemia. Heterozygous loss of chromosome 5q (del[5q]) is the most common cytogenetic abnormality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 38 publications
2
63
1
1
Order By: Relevance
“…25,39 However, a critical negative regulatory role for DIAPH1 is indicated by the observations that targeted knockout of the murine DIAPH1 ortholog Drf1 resulted in hyperproliferative myelodysplasia. 40,41 Consistent with this, DIAPH1 knockdown in cultured human MKs resulted in increased proplatelet formation. 17 In contrast, overexpression of a constitutively active DIAPH1, in which both the DID and DAD were deleted by artificial mutagenesis (mDiaDN3), reduced proplatelet formation in cultured human MKs.…”
Section: Org Fromsupporting
confidence: 59%
“…25,39 However, a critical negative regulatory role for DIAPH1 is indicated by the observations that targeted knockout of the murine DIAPH1 ortholog Drf1 resulted in hyperproliferative myelodysplasia. 40,41 Consistent with this, DIAPH1 knockdown in cultured human MKs resulted in increased proplatelet formation. 17 In contrast, overexpression of a constitutively active DIAPH1, in which both the DID and DAD were deleted by artificial mutagenesis (mDiaDN3), reduced proplatelet formation in cultured human MKs.…”
Section: Org Fromsupporting
confidence: 59%
“…One reason for this might be a different INAVA expression threshold required for distinct immunological outcomes. Expression/function threshold differences have been observed for various molecules (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that Lin -HLA-DR -CD33 + MDSCs were markedly expanded in the BM of MDS patients [114]. S100A8/ S100A9, which are known endogenous DAMPs [115,116], bind to CD33 to induce the expansion and activity of MDSCs [109,110]. Clonally distinct MDSCs in BM overproduce suppressive cytokines, such as IL-10 and TGF-β as well as nitric oxide (NO) and arginase, thereby contributing to the pathogenesis of MDS by inducing ineffective hematopoiesis.…”
Section: Tlr Signaling In Myelodysplastic Syndromementioning
confidence: 98%
“…The overexpression of CD14 also exacerbates the MDS disease phenotype in mice. These findings may explain why lenalidomide, an immunomodulatory agent, elicits a therapeutic response in patients with del(5q) MDS [110,111].…”
Section: Tlr Signaling In Myelodysplastic Syndromementioning
confidence: 99%
See 1 more Smart Citation